Irregular Word Formation of Lexical Innovations in James Dashner’s The Maze Runner - Dhyani Natasha Kartikasari; Ni Gusti Ayu Roselani (Lexicon, 2018)
This study investigates lexical innovations in The maze runner by James Dashner (2010), especially in terms of irregular word-formation techniques. 34 units of lexical innovations were found and classified according to their word classes: nouns, verbs, adjectives, and exclamations. The analysis focuses mainly on the examination of the word-formation processes undergone by the lexical units. The results reveal that four irregular word-formation techniques were used in the coinage of the new lexicon: compounding with left-headedness, compounding with unrecognizable constituent, compounding with irregular combination, and rhyming.